Detection of muscular system adverse reaction signals in sacubitril/valsartan treatment combined with statins - Fukun Zhao; Min Luo; Yuanmin Wang; Mu Su; Fei Tang (Frontiers Media S.A., 2024)
ObjectiveTo detect muscular system adverse reaction signals of sacubitril/valsartan treatment combined with statins (atorvastatin, rosuvastatin, simvastatin) to provide a reference for clinical administration.MethodsMultiplicative and additive models were used to mine the FDA's spontaneous reports database to detect signals of drug-drug interactions between sacubitril/valsartan and statins. SAS 9.4 software was used to conduct statistical tests for suspicious signals to determine whether the signals were statistically significant.ResultsA total of 8,883,870 adverse reaction reports were analyzed. The combinations "sacubitril/valsartan - simvastatin - musculoskeletal muscle pain" had statistically significant correlation signals in both models (P < 0.05). The combination "sacubitril/valsartan - atorvastatin - myopathy" and "sacubitril/valsartan-simvastatin - myopathy" had statistically significant correlation signal in the multiplicative model (P < 0.05).ConclusionCompared with a single drug, coadministration of sacubitril/valsartan with atorvastatin may increase safety risks to myopathy, with simvastatin may increase safety risks to the musculoskeletal pain and myopathy, which should be closely monitored in clinical practice.